Role of tyramine in calcium dynamics of GABAergic neurons and escape behavior in Caenorhabditis elegans - Yuko Kagawa-Nagamura (Zoological Letters, 2018)
Abstract Background Tyramine, known as a “trace amine” in mammals, modulates a wide range of behavior in invertebrates; however, the underlying cellular and circuit mechanisms are not well understood. In the nematode Caenorhabditis elegans (C. elegans), tyramine affects key behaviors, including foraging, feeding, and escape responses. The touch-evoked backward escape response is often coupled with a sharp omega turn that allows the animal to navigate away in the opposite direction. Previous studies have showed that a metabotropic tyramine receptor, SER-2, in GABAergic body motor neurons controls deep body bending in omega turns. In this study, we focused on the role of tyramine in GABAergic head motor neurons. Our goal is to understand the mechanism by which tyraminergic signaling alters neural circuit activity to control escape behavior. Results Using calcium imaging in freely moving C. elegans, we found that GABAergic RME motor neurons in the head had high calcium levels during forward locomotion but low calcium levels during spontaneous and evoked backward locomotion. This calcium decrease was also observed during the omega turn. Mutant analyses showed that tbh-1 mutants lacking only octopamine had normal calcium responses, whereas tdc-1 mutants lacking both tyramine and octopamine did not exhibit the calcium decrease in RME. This neuromodulation was mediated by SER-2. Moreover, tyraminergic RIM neuron activity was negatively correlated with RME activity in the directional switch from forward to backward locomotion. These results indicate that tyramine released from RIM inhibits RME via SER-2 signaling. The omega turn is initiated by a sharp head bend when the animal reinitiates forward movement. Interestingly, ser-2 mutants exhibited shallow head bends and often failed to execute deep-angle omega turns. The behavioral defect and the abnormal calcium response in ser-2 mutants could be rescued by SER-2 expression in RME. These results suggest that tyraminergic inhibition of RME is involved in the control of omega turns. Conclusion We demonstrate that endogenous tyramine downregulates calcium levels in GABAergic RME motor neurons in the head via the tyramine receptor SER-2 during backward locomotion and omega turns. Our data suggest that this neuromodulation allows deep head bending during omega turns and plays a role in the escape behavior in C. elegans.